Consumer motivation and satisfaction on recovery of outstanding water bills - Teo,, Ir. Seo Lin (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The purpose of this research paper is to examine and investigate consumer motivation and satisfaction for prompt payment of their water bills. It defines the motivating factors for looking at this area, reviews some recent related literatures and explores areas of overlapping interest.The aims and objectives of this study is to investigate the underlying problem(s) pertaining to non-payment of water bills by consumers with the aim of improving the existing recovery system and related work procedures in Kuching Water Board* (KWB), and to develop and recommend for adoption by KWB management a set of integrated applications that help the organization connect disparate system and more closely link the employees and the consumers. The findings and analysis from the consumer survey will provide the means for KWB management to reengineer its work processes particularly in the area of customer service for enhancing its bill (revenue) collection. The ultimate objective of this research is to instill consumer motivation for bill payment and subsequently contribute towards reduction of the considerable outstanding bill amount to an acceptable level. This research will also examine the impact of information and communication technology as a valuable tool and improvement agent on KWB 's organizational support system (workflow and procedures), consumer data management, consumer response management system, payment (billing & collection) system, and account management. With improvement and the enhancement of customer service and customer relations, the consumers will benefit from greater value service such as faster response time, cheaper water rates from cost reduction due to better integration of service and overall improved service. This research will contribute towards the reduction of outstanding water bills and inactive accounts. The improved revenue collection would make available the capital required for implementation of infrastructure projects, and the consumers would benefit from the upgrading of water production and distribution systems in the form of a more reliable and adequate supply of quality treated water.This research has discovered that, in general, consumers' perceived satisfaction of payment facilities (i. e. locality of payment counters,conditions of payment counters, sufficient counters, waiting time at counters) are somewhat more important than other motivational factors for consumer behavior in bill payment. Consumers' perceptions and feelings about `Process' (i. e. bill enquiry service, billing system, complaint receiving and processing system), `People' (i. e. efficient collection staff, courteous and responsive telephone operators, reliable customer service staff), and `Physical' (i. e. bill delivery and service complaint system) are all found to have a significant effect on the consumers' motivation towards bill payment but their effects are less profound than those factors related to payment facilities.